Socio-Ecological Analysis of Compliance with ARV Treatment in PLHIV in South Kalimantan - Imadduddin, Imadduddin; Noor, Zairin; Nugroho, Adi; Husaini, Husaini; Shadiqi, Muhammad Abdan (Jurnal Berkala Kesehatan, 2024)
In Indonesia, in 2021, the number of PLWHA found (419,551), adherence to taking antiretroviral medication (ARV) is the key to successful prevention of loss to follow-up (LFU) in people living with HIV (PLHIV). This research aims to comprehensively describe the factors that encourage and hinder adherence to ARV treatment in South Kalimantan from a stakeholder perspective. This research uses a qualitative approach with Focus Group Discussion (FGD) and in-depth interviews with 27 subjects from stakeholders, health workers, and non-governmental organizations/community organizations working in the field of HIV and AIDS in Banjar Regency, Banjarbaru City, Banjarmasin City, and Province. Data analysis uses the Miles and Huberman approach with the help of NVivo. The results of the study show the level of influence on ARV treatment adherence in PLWHA so that non-adherence is not only predicted at the individual level but is also known from the interpersonal, community, organizational and policy levels. For this reason, various intervention models are needed to increase adherence to ARV treatment in PLWHA. The conclusion shows that the most significant factor inhibiting adherence to ARV treatment in PLWHA is the organizational level.